Theatre-in-Education packages and secondary students’ knowledge of Yoruba orature in Ibadan metropolis - Ifeoluwa Akinsola (African Journal of Teacher Education)
This study was carried out to determine the effects of two Theatre-in-Education Packages (TiEPs) (Devised-for-students and Devised-by-students) on secondary students’ knowledge of Yoruba orature in the Ibadan metropolis, Nigeria. The moderating effects of Motivation for Yorùbá Orature (MYO) was also examined. The study adopted the Quasi experimental research design of the 3X2 factorial matrix. Three Local Government Areas (LGAs), out of the five existing in the Ibadan metropolis, were randomly selected. The simple random sampling technique was used to select six secondary schools (two from each LGA), while six intact classes of Senior Secondary II students (one per secondary school) were randomly assigned to TiEP Devised-for-students (87), TiEP Devised-by-students (115) and control (90) groups. The instruments used were Yoruba Orature Knowledge Test (r=0.81), Motivation for Yoruba Orature Questionniare (r=0.73) and instructional guides for implementing the TiEPs. Treatment lasted eight weeks. Data were analysed using descriptive statistics and Analysis of covariance at 0.05 level of significance. Results showed that treatment had significant main effect on students’ knowledge of Yoruba orature, in favour of students taught using the TiEP Devised-for-Students. The main effect of MYO and the interaction effect of treatment and MYO were not significant. Therefore, Yoruba language teachers should adopt the principles of TiEP Devised-for-Students in teaching Yoruba orature to their students.